PENGARUH JENIS GULA DAN PENAMBAHAN SARI BUAH ANGGUR PROBOLINGGO TERHADAP SIFAT FISIKOKIMIA, VIABILITAS BAKTERI YOGURT, DAN ORGANOLEPTIK YOGURT NON FAT - Tanaya, Catherine; Kusumawati, Netty; Nugerahani, Ira (Jurnal Teknologi Pangan dan Gizi, 2014)
Yogurt is a fermented dairy products which is made from milk fermented by Lactobacillus delbrueckii ssp. bugaricus and Streptococcus salivarius ssp. Sugar like isomalt has a lower caloric value than sucrose can be used as an alternative sweetener in Yogurt. The experimental design used Randomized Block Design (RBD) with two factors, sugar as the nest, and Probolinggo’s grapes which nested on sugar used. Type of sugar used was sucrose and isomalt whereas Probolinggo grape extract was added consisting of 3 levels of 5% (v/v), 10% (v/v), and 15% (v/v) with 4 replications. The parameters observed were pH, acidity, syneresis, total lactic acid bacteria and sensory preferences of taste and texture). The obtained data analyzed statistically by ANOVA (Analysis of Varians) at α = 5%. If there was a significant difference, then it was continued by DMRT (Duncan's Multiple Range Test) test to determine which level of treatment that gives significant differences. Different types of sweeteners produced gave no significant effect on pH, acidity, syneresis, ALT, and color but it had significant effect on the taste of Yogurt. While the difference in concentration of grape extract had significant effect for all parameters. As high as grape concentration, pH, acidity, viability of lactic acid bacteria, and color had increased. The best Yogurt from all treatment was sucrose Yogurt with grape extract 15%, which had ALT 9,8 log cfu/mL, pH 4,642, total acid 27,63oSH, syneresis 1,11%,and consumer perception defined as like for color, slightly favored for taste. For best isomalt Yogurt was Yogurt with grape extract 15%, which had ALT 9,8 log cfu/mL, pH 4,610, total acid 27,88oSH, syneresis 1,71%, and consumer perception defined as like for color, rather liked for taste.